Shifting burden of nasopharyngeal carcinoma: global patterns and forecasts to 2050 from the GBD 2021 - Zhou, Enhui; Xu, Feifei; Zhou, Tianjiao; Zhang, Jingyu; Song, Fan; Li, Jianxiang; Yi, Hongliang; Wang, Qingliang; Huang, Weijun (Frontiers in Oncology, 2026)
BackgroundNasopharyngeal carcinoma (NPC) exhibits pronounced geographical variation, with a high burden in specific regions. We assessed global, regional, and national trends in NPC burden from 1990 to 2021 and projected estimates to 2050.MethodsWe analyzed data from the Global Burden of Disease (GBD) 2021 study for 204 countries and territories across 21 regions. Age-standardized incidence rate (ASIR), age-standardized death rate (ASDR), and age-standardized disability-adjusted life-years (DALYs) rate were estimated, and temporal trends were assessed using estimated annual percentage change (EAPC) by socio-demographic index (SDI), sex, and age group. Future burden from 2022 to 2050 was projected using a Bayesian age–period–cohort model.ResultsIn 2021, there were 118,878 incident cases, 75,359 deaths, and 2,490,191 DALYs due to NPC globally. The global ASIR was 1.38 per 100,000 population (EAPC −1.06), the ASDR was 0.87 (EAPC −2.17), and the age-standardized DALYs rate was 28.91 (EAPC −2.29). Incidence rate peaked at ages 65–69 years (4.23 per 100,000 population), with consistently higher rates in males than in females. East Asia had the highest regional ASIR, and Japan bore the highest age-specific disease burden. Projections indicate continued declines in apparent ASDR and DALYs rates globally to 2050, but rising ASIR in males, particularly in East Asia and high-middle SDI regions.ConclusionsOver the past three decades, global mortality and disability burden from NPC have decreased, whereas incidence has increased in selected populations. The projected rise in ASIR among males in high-risk regions highlights the need for targeted interventions, equitable resource allocation, and sustained surveillance to mitigate future burden.